2010
DOI: 10.1165/rcmb.2008-0394oc
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylated Alanine-Rich C-Kinase Substrate (MARCKS) Protein Regulation of Human Neutrophil Migration

Abstract: Neutrophil migration into infected tissues is essential for host defense, but products of activated neutrophils can be quite damaging to host cells. Neutrophil influx into the lung and airways and resultant inflammation characterizes diseases such as chronic obstructive pulmonary disease, bronchiectasis, and cystic fibrosis. To migrate, neutrophils must reorganize the actin cytoskeleton to establish a leading edge pseudopod and a trailing edge uropod. The actin-binding protein myristoylated alanine-rich C-kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 50 publications
7
77
0
Order By: Relevance
“…The synthetic MANS peptide used in these studies is identical to the myristoylated 24-amino acid domain on the N-terminus of MARCKS, and has been shown previously to attenuate degranulation in airway epithelium (30) and leukocytes (17) and also to inhibit migration of inflammatory cells in vitro (18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthetic MANS peptide used in these studies is identical to the myristoylated 24-amino acid domain on the N-terminus of MARCKS, and has been shown previously to attenuate degranulation in airway epithelium (30) and leukocytes (17) and also to inhibit migration of inflammatory cells in vitro (18).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of other cell activities by RNS has been seen previously and could simply be a nonspecific response to a peptide. Nonetheless, RNS does serve as a useful negative control for MANS in a number of experimental settings (17,18,30). Since the function of the MARCKS amino terminus is thought to center on membrane binding, the inhibitory effects of MANS on MSC migration could be related to its interfering with MARCKS interaction with the cytoskeleton at the leading edge of the membrane in migrating cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIO-11006 was synthesized by PolyPeptide (Torrence, CA). A concentration of 50 µM for N-terminal MARCKS inhibitors was shown to have optimal effects on attenuating neutrophil motility in vitro (4,5), and showed efficacy in preliminary in vivo studies in LPSinjured mice, so this concentration of BIO-11006 (equivalent to z0.75 mg/kg) was chosen for time-related studies detailed subsequently here.…”
Section: Bio-11006mentioning
confidence: 99%
“…It was reported that the phosphorylation of MARCKS by protein kinase C results in the detachment of MARCKS from the membrane and suppress PIP2 by sequester manner (Gambhir et al, 2004;McLaughlin and Murray, 2005). At the same time it was also identified that in lungs, MARCKS especially phosphorylated MARCKS, plays a crucial role in controlling mucin secretion and inflammation (Eckert et al, 2010;Green et al, 2011;Li et al, 2001;Park et al, 2007;Singer et al, 2004). In addition, it was reported that phosphorylated MARCKS specifically regulate the cancer migration and metastasis (Chen et al, 2014;Chen and Rotenberg, 2010;Ghoul et al, 2006;Reddy et al, 2010;Techasen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%